Carbon coated titanium electrode for the electrolytic decoloration of methylene blue. (October 2016) - Zhang, Xiaoliang; Lin, Xiaowei; He, Miaomiao; Li, Hongliang; Wang, Weixuan; Yang, Sheng-Tao
Graphical abstract: Carbon nanoparticles were coated on Ti electrode by hydrothermal method to improve the electrolytic performance in the dye decoloration. Highlights: Ti electrode was modified with carbon to improve the electrolytic performance. Carbon amended Ti electrode could be used for the decoloration of various dyes. The electrolytic oxidation was via indirect pathway, where Cl − was oxidized into ClO − . Abstract: Electrolysis is widely adopted in water treatment. The major challenge of electrolysis technology focuses on developing better electrode materials. In this study, we reported that the hydrothermal coating of titanium electrode with carbon (C-Ti electrode) could significantly improve the decoloration performance of Ti electrode. The decoloration kinetics of C-Ti electrode was much faster than that of naked Ti electrode at the same current density. The presence of chloride electrolytes, e.g. NaCl and KCl, was crucial for the efficient electrolysis. The optimized pH for C-Ti electrode was pH 7. Beyond methylene blue, C-Ti electrode showed high decoloration performance for other dyes, such as congo red, acidic blue 92 and remazol brilliant blue R. Mechanistically, the electrolytic oxidation of MB was mainly via indirect pathway, where Cl − was oxidized into ClO − for the oxidation of other substances. Moreover, the performance of C-Ti electrode largely remained in the recycling evaluations. The implication to the applications of C-Ti electrode in water treatment is discussed.